How to conceptualize an alternative to platform capitalism according to the re-embedding process of K. Polanyi ? [Comment penser l'alternative au capitalisme de plateforme dans une logique de réencastrement polanyien ?] - Aufrère, Laura; Eynaud, Philippe; Maurel, Lionel; Vercher-Chaptal, Corinne (CEPN Working Papers, 2020)
The article considers alternatives to platform capitalism in a logic of Polanyian re-embedding. Stemming from case studies in the car-pooling, delivery and hosting sectors, the results uncover hybrid business models in which the market principle is used in the service of reciprocal logic. Rejecting the formal algorithmic rationality of capitalist platforms, the alternatives seek to align individual and collective behavior with values of solidarity and goals of general interest. They are experimenting with original methods of scaling up, based on the federation of communities, respectful of their anchoring in the substantive economy. The results make it possible to think of complementarities between different forms of embedding likely to be played out on several scales, and open perspectives for rethinking public policies vis-à-vis the experiments of the solidarity economy and the commons.
Keywords: coopérativisme de plateforme; decommodification; digital platforms; démar- chandisation; plateformes numériques; platform cooperativism; re-embedding; reciprocity; ré-encastrement; réciprocité; substantive economy; économie substantive

The surplus approach, Polanyi and institutions in economic anthropology and archaeology - Cesaratto, Sergio; Bucchianico, Stefano Di (Department of Economics University of Siena, 2020)
This paper was inspired long ago by Jared Diamond (1997), and in particular by his extensive use of the concept of economic surplus as the key to the development of civilization. Unfortunately, Diamond does not mention the origin of the concept in classical and pre-classical economics, nor does he pay much attention to debates in economic anthropology about the role of economic analysis in studying primitive and ancient economic formations. These debates were the subject of a recent book by Cedrini & Marchionatti (2017), who dispute the neoclassical “imperialist” attempt to occupy the territory of economic anthropology. The authors rely on the institutionalist background provided by Karl Polanyi and his school and by other anthropologists of similar inspiration. Polanyians, however, fail to complete their institutional analysis by anchoring it to the changing modes of generation and distribution of the economic surplus. Yet their emphasis on the need to introduce institutions from the beginning, when speaking of economic surplus, should be taken into consideration by the classical surplus approach
Keywords: Marx; Polanyi; Sraffa; economic anthropology; economic archaeology; surplus approach